He Rourou Whai Painga, an Aotearoa New Zealand dietary pattern for metabolic health and whānau wellbeing: protocol for a randomized controlled trial - Lithander, Fiona E.; Parry Strong, Amber; Braakhuis, Andrea; Worthington, Anna; Foster, Meika; Rolleston, Anna; Davies, Cheryl; Mullaney, Jane; Ross, Cecilia; Conroy, Denise; Merry, Troy L.; Gearry, Richard; et al. (Frontiers in Nutrition, 2023)
Background: Cardiometabolic diseases are highly prevalent in Aotearoa New Zealand. Dietary intake is a modifiable risk factor for such diseases and certain dietary patterns, specifically the Mediterranean diet (MedDiet), are associated with improved metabolic health. This study aims to test whether an intervention including a Mediterranean dietary pattern incorporating high quality New Zealand foods (NZMedDiet pattern) and behaviour change science can improve the metabolic health of participants and their household/whānau. Methods and analysis: This is a multi-centre, three-stage trial with two parallel group superiority randomized controlled trials (RCTs), and a longitudinal cohort study embedded within the trial design. The first RCT (RCT 1) is a comparison of the NZMedDiet pattern implemented using behaviour science compared to usual diet for 12 weeks. The Behaviour Change Wheel was used to select and implement strategies to support participant adherence to the NZMedDiet, such as web-based nutrition education on healthy shopping and cooking., Tand the second (RCT 2) compares is web-based nutrition education and online social support to compared to no online social support for 12 weeks, administered to participants immediately following RCT 1. The third stage is a longitudinal cohort study where all participants are followed from the beginning of their start of the active interventionRCT 1 for 12 months in total. The primary outcome measure for each stage is the metabolic syndrome severity score (MetSSS). The duration of enrolment is 12-15 months. The total recruitment target is 200 index participants and their household/whānau members who participate with them, and the primary analyses will be intention to treat on index participants. Discussion: The trial will test whether the NZMedDiet pattern and behaviour change support improves the cardiometabolic health of people in Aotearoa New Zealand.